Granulocyte colony-stimulating factor protects mice during respiratory virus infections. - Tamar Hermesh; Thomas M Moran; Deepika Jain; Carolina B López (PLoS ONE, 2012)
A burst in the production of pro-inflammatory molecules characterizes the beginning of the host response to infection. Cytokines, chemokines, and growth factors work in concert to control pathogen replication and activate innate and adaptive immune responses. Granulocyte colony-stimulating factor (G-CSF) mobilizes and activates hematopoietic cells from the bone marrow, and it has been shown to mediate the generation of effective immunity against bacterial and fungal infections. G-CSF is produced at high levels in the lungs during infection with influenza and parainfluenza viruses, but its role during these infections is unknown. Here we show that during infection of mice with a non-lethal dose of influenza or Sendai virus, G-CSF promotes the accumulation of activated Ly6G+ granulocytes that control the extent of the lung pro-inflammatory response. Remarkably, these G-CSF-mediated effects facilitate viral clearance and sustain mouse survival.